2014
DOI: 10.1002/ijc.29277
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplement use and colorectal cancer risk: A systematic review and meta‐analyses of prospective cohort studies

Abstract: Use of dietary supplements is rising in countries where colorectal cancer is prevalent. We conducted a systematic literature review and meta-analyses of prospective cohort studies on dietary supplement use and colorectal cancer risk. We identified relevant studies in Medline, Embase and Cochrane up to January 2013. Original and peer-reviewed papers on dietary supplement use and colorectal cancer, colon cancer, or rectal cancer incidence were included. "Use-no use"(U-NU), "highest-lowest"(H-L) and "dose-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 63 publications
(146 reference statements)
3
76
0
2
Order By: Relevance
“…Vitamin C plays a key role in the production of collagen and its deficit upsets the integrity of intracellular matrix and promotes tumor proliferation. Heine-Broring et al (25) suggested an inverse correlation between risk of CRC and deficiency of vitamins A, E, and C, similar findings were observed in this study. On the other hand, recently, no association was found between supplementation of these dietary vitamins and risk of CRC (26).…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin C plays a key role in the production of collagen and its deficit upsets the integrity of intracellular matrix and promotes tumor proliferation. Heine-Broring et al (25) suggested an inverse correlation between risk of CRC and deficiency of vitamins A, E, and C, similar findings were observed in this study. On the other hand, recently, no association was found between supplementation of these dietary vitamins and risk of CRC (26).…”
Section: Discussionsupporting
confidence: 91%
“…Both a high intake of red meat and a low intake of calcium were associated with polyp growth [32]. Food supplementation such as multivitamin intake and calcium supplementation also seems to be beneficial in this context [33]. Alcohol consumption was associated with an increased risk for advanced adenomas [34].…”
Section: Factors Influencing the Adrmentioning
confidence: 99%
“…As recognized by the general public, Ca supplementation, apart from decreasing the risk of osteoporosis, may also have an impact on cancer prevention and play a role in the decrease in cardiovascular disorders [6,12]. These assumptions are, however, only partially supported and require further studies [11,13,14]. Moreover, some studies support the view that Ca supplementation may even increase the risk of adverse cardiovascular events and have a deteriorating effect on lipid levels [15,16].…”
Section: Discussionmentioning
confidence: 99%